2011
DOI: 10.1002/wcc.134
|View full text |Cite
|
Sign up to set email alerts
|

Public perceptions and governance of controversial technologies to tackle climate change: nuclear power, carbon capture and storage, wind, and geoengineering

Abstract: The role carbon emissions play in contributing to climate change makes clear the necessity for a global reconsideration of current modes of energy production. In recent years, as concerns over the threats of climate change (CC) have become more acute, four technologies have notably risen to the forefront of academic and public discourse: nuclear power, carbon capture and storage (CCS), wind power, and geoengineering. The particular interest of these four approaches lies in the fact that they reflect both energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 54 publications
0
50
0
Order By: Relevance
“…First, it also materializes specific technological innovations (Bauer, 1995), devised in order to perform that task. While the use of renewable sources for the generation of energy, such as wind or water, is already a very old practice (Poumadère, Bertoldo, & Samadi, 2011), the design, size, and embeddedness at different geographical scales of current infrastructures for the generation of electricity or heat from those sources, namely within centralised models of electricity systems, are new and unfamiliar to most individuals and groups (Poumadère et al, 2011). These new 9 artefacts are being deployed in specific historical and societal contexts, in which different representations co-exist about energy, space and place, landscape, citizenship and so forth, and where particular individuals and groups will thus attribute distinct meanings to the same technologies (Pinch & Bijker, 1987).…”
Section: Renewable Energy At the Crossroads Of Legal And Techno-scienmentioning
confidence: 99%
“…First, it also materializes specific technological innovations (Bauer, 1995), devised in order to perform that task. While the use of renewable sources for the generation of energy, such as wind or water, is already a very old practice (Poumadère, Bertoldo, & Samadi, 2011), the design, size, and embeddedness at different geographical scales of current infrastructures for the generation of electricity or heat from those sources, namely within centralised models of electricity systems, are new and unfamiliar to most individuals and groups (Poumadère et al, 2011). These new 9 artefacts are being deployed in specific historical and societal contexts, in which different representations co-exist about energy, space and place, landscape, citizenship and so forth, and where particular individuals and groups will thus attribute distinct meanings to the same technologies (Pinch & Bijker, 1987).…”
Section: Renewable Energy At the Crossroads Of Legal And Techno-scienmentioning
confidence: 99%
“…Fourthly, it is assumed that new institutional arrangements for the proper regulation of geoengineering can in principle be built on existing international instruments used to regulate transboundary issues, and more generally can be accommodated within the structures of democratic national and international governance (see discussion in Virgoe, 2 2009). Fifthly, it is assumed that survey, qualitative and public engagement research can help clarify public attitudes to solar radiation management (see Ipsos-MORI, 2010;Leiserowitz et al, 2010;Mercer et al, 2011;Parkhill and Pidgeon, 2011;Pidgeon et al, 2012;Poumadere et al, 2011;Spence et al, 2010), and that the main role of such research should be to incorporate value-based considerations about geoengineering into decision-making (see Corner et al, 2012 for a review). Notwithstanding the importance of such research, what has been insufficiently explored is how public engagement methods can be used to explore the kinds of world that solar radiation management techniques might bring into being, and thereby to critically explore the assumptions that underpin governance debates around this technology.…”
Section: The Debate About Geoengineering Governancementioning
confidence: 99%
“…The first is primarily quantitative and maps public opinions or perceptions. A few surveys have estimated lay knowledge or perceptions of GE (NERC, 2010;Kahan et al, 2012;Pidgeon et al, 2012;Merk et al, 2014;Wright et al, 2014; see also Poumadere et al, 2011), finding that only a few per cent of respondents had heard of GE and that even fewer knew about its basic principles. A survey of public perceptions of GE in the US, the UK and Canada found that only 8% of respondents were somewhat familiar with GE (Mercer et al, 2011).…”
Section: Public Understanding Of Geoengineering: An Emerging Researchmentioning
confidence: 99%